Between transparency and surveillance: Politics of the secret. (May 2016) - Borradori, Giovanna
The recent wave of whistleblowers and cyber-dissidents, from Julian Assange to Edward Snowden, has declared war against surveillance. In this context, transparency is presented as an attainable political goal that can be delivered in flesh and bones by spectacular and quasi-messianic moments of disclosure. The thesis of this article is that, despite its progressive promise, the project of releasing classified documents is in line with the Orwellian cold war trope of Big Brother rather than with the complex geography of surveillance today. By indicting the US federal government as the principal agent of surveillance, the 'logic of the leak' obfuscates that today's surveillance is conducted mostly by the private sector in the form of dataveillance. What should we think, then, of this new fetish of transparency? Is it a symptom of the castigation of a desire for surveillance, the wish to be constantly observed and closely inspected? I claim that the meaning of the 'expository society', as Bernard Harcourt calls it, depends on how we interpret secrets. For secrets are not only temporary conditions of occultation that can, and should, be indiscriminately exposed, but sites of agency. In this perspective, the emancipatory promise hangs on the right to the secret, assumed as the right not to answer and not to belong.